¿A quién se le enseña física moderna?, una mirada en instituciones educativas de Bogotá-Colombia - Prieto, Ana Milena; Organista, Orlando (Revista Científica, 2011)
﻿There is data related to the teaching of modern physics in engineering careers in institutions of Bogotá. These data are interpreted in order to approach the question; what is the diffusion of modern physics in a curricular level, in the professional formation of engineers? .This diagnostic will take us to propose different reflections around the teaching or not of modern ideas of physics in this context.